ANALYSIS OF PLANNING STUDY AND DEVELOPMENT OF INDIVIDUAL TRANSFERABLE QUOTA SYSTEM (ITQ) IN REALIZING QUOTA-BASED SUSTAINABLE FISHERIES - Ramadian, Afzil; Sutyawan, Fery; Sara, La (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2022)
Fish exploitation in Indonesia is already at a very alarming level. Catching at full capacity and even excess occurs in almost all fisheries management areas. One of the foreign government's efforts to overcome similar problems is by conducting ITQ. This research approach uses qualitative descriptive qualitative specifications. Data analysis techniques miles and huberman data triangulation: reduction, data presentation, verification carried out to find out the analysis of planning studies and the development of the Individual Transferable Quota (ITQ) system in realizing quota-based sustainable fisheries. This activity was carried out in collaboration with the grow fisheries training program and the university of Akureyri. The training was held from 19 - 28 May 2022 at the Marine and Freshwater Research Institute building and the University of Akureyri. The conclusion of this study is that the condition of the Indonesian seas, which is starting to deteriorate due to excessive and illegal fishing, requires firm action. It is hoped that the ITQ system can be implemented in Indonesia. So that when fishing is not done excessively.